PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TAKE AND GIVE TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XII IPA SMAN 2 MERANGIN TAHUN PELAJARAN 2019/2020 - Arista Ratih; Rivo Yulse Viza; Dika Sumanti (BIOCOLONY, 2019)
This research is motivated by the interaction of learning in the classroom that takes place in one direction, so that students take for granted the information provided by the teacher. Student responses to learning tend to be low. During the learning process, student participation only records and listens to the teacher's explanation. This has an impact on learning outcomes. This is evidenced from the UAS learning outcomes of class XI students of SMAN 2 Merangin, which are still low and have not yet reached KKM 75. Therefore this study aims to describe the results of learning biology with the type of cooperative learning model Take and Give better than the results of learning biology with the conventional model of class XII science students of SMAN 2 Merangin 2019/2020 school year. This research was conducted with a quantitative approach with a posttest-only control design research design. The population in this study were all students of class XII IPA of SMA N 2 Merangin consisting of three classes, from class XII IPA 1, and XII IPA 2, and XII IPA 3, totaling 68 students. After steps are taken in determining the sample class, the researcher obtains a combination of the AC class, where A (XII IPA 1) becomes the experimental class, and class C (XII IPA 3) becomes the control class. Data collection techniques used to obtain the data needed is a test (test). Before being used the test was analyzed using the validity test, distinguishing power, difficulty index, and reliability test. Based on the results of hypothesis testing it is known that the price of tcount> ttable or 2.948> 2.016. From these results it can be concluded that there is an influence of the Take and Give learning model on the learning outcomes of biology class XII students of SMAN 2 Merangin 2019/2020 school year.